2023
DOI: 10.3390/jmse11020301
|View full text |Cite
|
Sign up to set email alerts
|

Research of Vibration Effects on a Hydraulic Valve in the Pressure Pulsation Spectrum Analysis

Abstract: This paper identifies mechanical vibrations occurring in the operating environment of hydraulic systems used in marine engineering. Particular attention was paid to the influence of periodic vibrations on changes in the amplitude-frequency spectrum in a marine hydraulic system. For the case of analysing the effect of vibration on changes in the pressure pulsation spectrum with a proportional directional valve, a modified mathematical model was used. Experimental results were presented and compared with the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Materials 2024, 17, x FOR PEER REVIEW 3 of 15 no expansion limits, so far. Recently, it has been shown that detailed studies of low-frequency vibrations can be very helpful in characterizing the performances of complex mechanical devices [19,20]. The remainder of the paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials 2024, 17, x FOR PEER REVIEW 3 of 15 no expansion limits, so far. Recently, it has been shown that detailed studies of low-frequency vibrations can be very helpful in characterizing the performances of complex mechanical devices [19,20]. The remainder of the paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Our work also focuses on the general field of the application of resonances, a field that has known no expansion limits, so far. Recently, it has been shown that detailed studies of low-frequency vibrations can be very helpful in characterizing the performances of complex mechanical devices [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Using these functions, it is possible to derive the pressure spectrum, the velocity of the fluid flow, and the velocity of sound in the contained fluid. In a most recent study, Stosiak et al [41] addressed an interesting topic of external mechanical vibrations causing excitation to a directional control valve in a heavy-duty military vehicle. The main conclusion mentions that a cushion made of a material with a high stiffness and damping mounted between the casing and the centering spring can lead to reduction of the vibration on the valve spool.…”
Section: Introductionmentioning
confidence: 99%
“…The above input limits make the positioning control of the hydraulic support pushing system based on the electrohydraulic directional control valve more difficult. The common positioning control system of the valve-controlled cylinder can be divided into high-speed switch valve, switch array control system [7][8][9], servo and proportional control system [10,11], electromagnetic directional valve, and electrohydraulic directional control valve control system according to the type of control element.…”
Section: Introductionmentioning
confidence: 99%